2001
DOI: 10.1093/pcp/pce061
|View full text |Cite
|
Sign up to set email alerts
|

A Large Family of Class III Plant Peroxidases

Abstract: Class III plant peroxidase (POX), a plant-specific oxidoreductase, is one of the many types of peroxidases that are widely distributed in animals, plants and microorganisms. POXs exist as isoenzymes in individual plant species, and each isoenzyme has variable amino acid sequences and shows diverse expression profiles, suggesting their involvement in various physiological processes. Indeed, studies have provided evidence that POXs participate in lignification, suberization, auxin catabolism, wound healing and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
545
0
36

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 788 publications
(597 citation statements)
references
References 85 publications
16
545
0
36
Order By: Relevance
“…6). POX catalyse oxidoreduction reactions of various substrates via H 2 O 2 ; however, they are also known to be involved in ROS production under specific conditions (Hiraga et al 2001). POX can contribute to resistance against pathogens in various pathosystems (Baysal et al 2005), whereas localized production of H 2 O 2 and superoxide radical belong among the first cytologically and histochemicaly detected responses of plant tissue on penetration of pathogen.…”
Section: Involvement and Activity Of Antioxidant Enzymes In Plant Sysmentioning
confidence: 99%
“…6). POX catalyse oxidoreduction reactions of various substrates via H 2 O 2 ; however, they are also known to be involved in ROS production under specific conditions (Hiraga et al 2001). POX can contribute to resistance against pathogens in various pathosystems (Baysal et al 2005), whereas localized production of H 2 O 2 and superoxide radical belong among the first cytologically and histochemicaly detected responses of plant tissue on penetration of pathogen.…”
Section: Involvement and Activity Of Antioxidant Enzymes In Plant Sysmentioning
confidence: 99%
“…6,7 In the presence of H 2 O 2 (the common e ¡ acceptor) and a variety of e ¡ -donating substrates, plant POXs may achieve a great deal of oxidation reactions essential for the functions of living cells, 5 possibly via production and localization of certain POX isoforms at specific timing, so that the living plants can respond to and combat a wide variety of stressful challenges with biotic or abiotic nature. 11,12 In the absence of H 2 O 2 -requiring reactions, plant POXs are still capable of production of ROS (O 2 ¡ and derived H 2 O 2 ) through the oxygen-requiring cycle involving specific e ¡ donors such as indole-3-acetic acid (IAA), a natural auxin. [13][14][15] The idea on the IAA-dependent reduction of native plant POX to ferrous enzyme intermediate has been proposed by Smith and his colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis could be the possible role of stigma-specific peroxidases in the defence of stigma against pathogen attack. In literature it is known that some peroxidases are involved in defence response by induction or up-regulation in relation to stress and hypersensitive response [1]. For instance, a peroxidase of Capsicum annum L. CaPrx02 resulted expressed during response against pathogen attack regulating H 2 O 2 levels [49], while a research in almond demonstrated the expression of peroxidases in the pistil in relation with pathogenesis response [50], enforcing the idea of a putative role of stigma-specific peroxidases in defence mechanisms, when the pistil is able to receive pollen.…”
Section: Discussionmentioning
confidence: 99%